Metabolic requirements of Th17 cells and of B cells: Regulation and defects in health and in inflammatory diseases - Bystrom, Jonas; Taher, Taher E.; Henson, Sian M.; Gould, David J.; Mageed, Rizgar A. (Frontiers in Immunology, 2022)
The immune system protects from infections and cancer through complex cellular networks to facilitate specific and timely responses. For this aim, immune cells require well-developed mechanisms of energy generation. The immune system itself can also cause disease when defect regulation results in emergence of autoreactive lymphocytes. Recent studies provide insights into how differential patterns of immune cell responses are associated with selective metabolic pathways. This review will examine the changing metabolic requirements of Th17 cells and of B cells at their different stages of development and activation. Both cells play crucial roles in mediating diseases through the production of autoantibodies that form immune complexes with self-antigens, activate the production of proinflammatory mediators and precipitate chronic inflammation. In health, B cells produce antibodies and cytokines and present antigens to T cells to mount protective immunity. Th17 cells, on the other hand, provide protection against extra cellular pathogens at mucosal surfaces but can also drive inflammatory processes. These cells can also promote the differentiation of B cells to plasma cells. Metabolism-regulated checkpoints at different stages of the development ensure the that self-reactive B cells clones and needless production of IL-17 are prevented. The metabolic regulation of the two cell types has similarities, e.g. the utility of HIF1α during low oxygen tension, to prevent autoimmunity and regulate inflammation. There are also clear differences, as Th17 cells only are vulnerable to the lack of certain amino acids. B cells, unlike Th17 cells, are dependent of mTORC2 to function. Significant knowledge has recently been gained, particularly for Th17 cells, on how metabolism regulates these cells through influencing the epigenome. Metabolic dysregulation of Th17 cells and B cells can lead to chronic inflammation. Disease associated alterations in the genome can cause dysregulation on metabolism and thereby result in epigenetic alterations in these cells. Recent studies highlight how pathology can result from the cooperation between the two cell types but only few have so far addressed the key metabolic alterations in such settings. Knowledge of the impact of metabolic dysfunction on chronic inflammation and pathology can reveal novel therapeutic targets to treat such diseases.